Kajian Eksegetikal Amanat Agung menurut Matius 28:18-20 - Susanto Dwiraharjo (Sekolah Tinggi Teologi Baptis, Jakarta, 2019)
The Great Commission is an integral part of the life of believers. This is the message of Christ for all citizens of the kingdom of God. It is called the Great Commission that does not mean its position is more important than other parts of the Bible. But this has demands that every believer must do. On the other hand it can be confirmed that the Great Commission is nothing but the pulse of the believer. In Matthew 28: 18-20, discussions about the Great Commission can be divided into three main parts. These three parts stand to support one another, and refer to the central theme of the Great Commission. First, the Great Commission is based on the authority of the Father bestowed on Christ. Second, the Great Commission is a continuous activity that is always inherent in the lives of believers. When the Great Commission is sustained by the ability or inclusion of Christ. These three things are the essence or essence of the interpretation of the Great Commission in the daily life of believers. Abstrak Amanat Agung adalah bagian integral hidup orang percaya. Ini adalah amanat Kristus bagi semua warga kerajaan Allah. Disebut Amanat Agung itu bukan berarti kedudukannya lebin penting dari bagian lain di dalam Alkitab. Namun ini memiliki tuntutan yang harus dilakukan oleh setiap orang percaya. Di sisi lain dapat dipertegas bahwa Amanat Agung tidak lain adalah denyut nadi orang percaya. Dalam Matius 28:18-20, pembahasan tentang Amanat Agung dapat dibagi ke dalam tiga bagian utama. Ketiga bagian ini berdiri untuk saling menopang satu dengan yang lain, dan mengacu pada tema sentral tentang Amanat Agung. Pertama, Amanat Agung itu didasarkan pada otoritas Bapa yang dilimpahkan kepada Kristus. Kedua, Amanat Agung itu merupakan aktivitas berkesinambungan yang selalu melekat dalam hidup orang percaya. Ketika Amanat Agung itu ditopang oleh abilitas atau penyertaan Kristus. Ketiga hal ini merupakan hakekat atau intisari dari intepretasi Amanat Agung dalam hidup harian orang percaya.